INFLUENCE of polyoxypropylenepolyolS On water objects - V.V. Babienko; L.V. Anishchenko; V.L. Mykhaylenko (Проблеми екології та медицини)
The article describes the results of toxicological and epidemiological characteristics of the new group and polyoxypropylene substantiated forecast of sanitary and epidemiological welfare of the water bodies. The study is based on research of biological action of polyols on the body of warm-blooded animals in the conditions of acute and subacute experiments, the effect of polyols on the organoleptic properties of water and sanitary water reservoirs regime. The study showed that the basis of the mechanism of biological action is polyoxypropylene stimulation of lipid peroxidation on the background of the depletion of the antioxidant system, violation of the structure of cell membranes, decrease of activity of membrane-bound enzymes, a violation of bioenergy, oxidative phosphorylation and redox processes in the body of warm-blooded animals. Leading pathogenetic link the formation of structural and metabolic disorders in the body are activated free radical lipid peroxidation, inhibition of antioxidant systems and energy processes that underlie the development of tissue hypoxia and reduced recovery processes.